(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the legal epistemology, reasoning methods, and interpretive paradigms underlying the dissenting opinion in the decision. The study uses a normative legal method with a statutory, case, and legal philosophy approach. The primary legal materials include the Constitutional Court Decision Number 90/PUU-XXI/2023, the 1945 Constitution of the Republic of Indonesia, and related laws and regulations. Secondary legal materials are obtained from books, scientific journals, and relevant legal documents. The analysis is conducted qualitatively through legal interpretation, analysis of legal arguments, and a study of legal philosophy to identify the epistemological basis and reasoning patterns used in the dissenting opinion. The results show that the dissenting opinion is built on a foundation of legal certainty and respect for an open legal policy as the limit of judicial authority. The minority judges consistently applied judicial restraint and criticized the Constitutional Court’s shift to a positive legislative role. Furthermore, there are differing paradigms in interpreting the principle of equality before the law, demonstrating a conflict between formalistic approaches and substantive justice. These findings confirm that dissenting opinions are not merely a record of differing opinions, but serve as academic and constitutional instruments to uphold the principles of separation of powers and a democratic rule of law.